5´XP sRNA-seq: efficient identification of transcripts with and without 5´ phosphorylation reveals evolutionary conserved small RNA. Issue 11 (2nd November 2021) - Kugelberg, Unn; Nätt, Daniel; Skog, Signe; Kutter, Claudia; Öst, Anita
ABSTRACT: Small RNA (sRNA) sequencing has been critical for our understanding of many cellular processes, including gene regulation. Nonetheless, the varying biochemical properties of sRNA, such as 5´ nucleotide modifications, make many sRNA subspecies incompatible with common protocols for sRNA sequencing. Here we describe 5XP-seq that outlines a novel strategy that captures a more complete picture of sRNA. By tagging 5´P sRNA during library preparation, 5XP-seq combines an open approach that includes all types of 5ʹ-terminal modifications (5´X), with a selective approach for 5-phosphorylated sRNA (5´P). We show that 5XP-seq not only enriches phosphorylated miRNA and piRNA but successfully discriminates these sRNA from all other sRNA species. We further demonstrate the importance of this strategy by successful inter-species validation of sRNAs that would have otherwise failed, including human to insect translation of several tRNA (tRFs) and rRNA (rRFs) fragments. By combining 5´ insensitive library strategies with 5´ sensitive tagging, we have successfully tackled an intrinsic bias in modern sRNA sequencing that will help us reveal the true complexity and the evolutionary significance of the sRNA world.